Language in the legal process (Palgrave Macmillan, 2004)
Linguists and lawyers from a range of countries and legal systems explore the language of the law and its participants, beginning with the role of the forensic linguist in legal proceedings, either as expert witness or in legal language reform. Subsequent chapters analyze different aspects of language and interaction in the chain of events from a police emergency call through the police interview context and into the courtroom, as well as appeal court and alternative routes to justice. A broad-based, coherent introduction to the discourse of language and law that is ideal for students studying forensic linguistics or language and law, or who want to relate their more general discourse studies to real-life situations. This book demonstrates the methods of linguistic analysis in whole range of discourse and communication encounters in the legal process, presented by world experts in the field.